2020
DOI: 10.3329/bjme.v11i2.49248
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Teaching-learning in Undergraduate Medical Education in Bangladesh - Views of Stakeholders

Abstract: This descriptive type of cross-sectional study was carried out in 4 government and 4 non-government medical colleges of Bangladesh to assess the quality of undergraduate medical education. The study was conducted during the period of July 2018 to June 2019. The total sample size was 576, out of which there were 440 fifth year medical students, 114 clinical teachers and 22 Key informants. Convenience sampling technique was adopted. Two self - administered semi- structured questionnaires and one in-depth-intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…This study has identified several key themes to present the contributory factors for positive learning. These are learning from patients, learning from ward-boys and mistresses, evaluation forms, studying theory supports clinical practice [21], training in skill lab supports clinical practice, warm welcome and cooperation from senior nurses, learning from the doctors, and teaching methods [11] (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has identified several key themes to present the contributory factors for positive learning. These are learning from patients, learning from ward-boys and mistresses, evaluation forms, studying theory supports clinical practice [21], training in skill lab supports clinical practice, warm welcome and cooperation from senior nurses, learning from the doctors, and teaching methods [11] (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…A literature review has revealed a few studies on students’ challenges during clinical learning in Bangladesh [10, 11]. Identifying the obstacles that nursing students confront in all facets of the clinical learning environment may help enhance skills and the planning quality and advancement of students [2].…”
Section: Introductionmentioning
confidence: 99%
“…Participants mentioned that the buildings of medical colleges and their affiliated hospitals, especially in the periphery were not purpose-built. Studies from Bangladesh 23 and India 24 pointed out similar challenges of inadequate infrastructure, insufficient staff, and weak logistics management in accreditation implementation. Implementing a national accreditation program requires considerable financial resources.…”
Section: A H E a D O F P R I N Tmentioning
confidence: 99%